Consilience in Developing a Multidisciplinary Framework of Spirituality: Scientific Commentary on Chatlos - Winkelman, Michael James (Zygon, 2025)
Calvin Chatlos provides a novel consideration of spiritual experiences and attempts to find ontological grounds to span these concerns within science, philosophy, and theology. Conceptualization of spiritual experiences in terms of self-worth presents interesting avenues for future considerations of the role of self in explaining spirituality but also faces several validity challenges. Resolving ontological issues requires first addressing epistemological issues regarding the nature of knowledge, which permits an interdisciplinary investigation of spirituality and the soul. The cross-cultural validity of such constructs requires their basis in neurophenomenology, neurognostic perspectives, and neurological processes that engage naturalist perspectives on the foundations of religion.